Long-term outcomes following stereotactic body radiotherapy boost for oropharyngeal squamous cell carcinoma. (3rd June 2019) - Baker, Sarah; Verduijn, Gerda M.; Petit, Steven; Sewnaik, Aniel; Mast, Hetty; Koljenović, Senada; Nuyttens, Joost J.; Heemsbergen, Wilma D.
Abstract: Background/purpose: To determine the efficacy and toxicity profile of a stereotactic body radiotherapy (SBRT) boost as a first line treatment in patients with oropharyngeal squamous cell carcinoma (OPSCC). Materials and methods: We performed a retrospective cohort study in 195 consecutive OPSCC patients with T1-small T3 disease, treated at Erasmus MC between 2009 and 2016 with a SBRT (3 × 5.5 Gy) boost after 46 Gy IMRT. Primary endpoints were disease-specific survival (DSS) and Grade ≥3 toxicity (Common Terminology Criteria). The Kaplan-Meier method and Cox regression model were applied to determine rates and risk factors. Results: The median follow-up was 4.3 years. Treatment compliance was high (100%). Rates of 5-year DSS and late grade ≥3 toxicity were 85% and 28%, respectively. Five-year overall survival was 67%. The most frequently observed toxicities were mucosal ulceration or soft tissue necrosis ( n  = 30, 5 year 18%), dysphagia or weight loss ( n  = 18, 5 year 12%) and osteoradionecrosis ( n  = 11, 5 year 9%). Current smoker status (hazard ratio [HR] = 2.9, p  = .001) and Charlson Comorbidity Index ≥2 (HR = 1.9, p  = .03) were was associated with increased toxicity risk. Tooth extraction prior to RT was associated with increased osteoradionecrosis risk (HR = 6.4, p  = .006). Conclusion: We reported on outcomes in the largest patient series to date treated with a hypofractionated boost for OPSCC. Efficacy was good with survival rates comparable to conventionally fractionated (chemo)radiotherapy. Grade ≥3 toxicity profiles showed high rates of soft tissue necrosis and osteoradionecrosis. Strategies to mitigate severe toxicity risks are under investigation to improve the tolerability of the SBRT boost.